VOCATIONAL TRAINING FOR CLAY PLASTER IN EUROPE : A GROWING NETWORK AND PEDAGOGICAL AND ADMINITRATIVE TOOLS TO HELP DISSEMINATION OF COMPETENCE AND RECOGNITION OF LEARNING OUTCOMES - Didier, Lydie; Duoline, Alexandre; Herz, Uta; RügerBurkard (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
There is a growing need for training trainers, so as to guarantee the quality not only of the training, but also of the earthbuilding construction activities resulting from it in Europe. Clay plaster courses act as a catalysator, opening the doors for other earth building techniques. The ultimate goal is to introduce earthbuilding techniques into initial vocational qualifications. The present paper addresses (a) the network of trainers and of training centres, that developed out of successive partnerships during several European projects and (b) the tools elaborated within these projects. The Leonardo da Vinci EU-project “Clay Plaster”, from 2002 to 2005, produced a complete pedagogical tool, available in six languages. These files, available on CD-Rom, have since been used in many different learning contexts across Europe. Since 2006, training courses for trainers bring together twice a year teachers and multiplicators across Europe, thanks to individual grants from the Grundtvig progamme. Since 2005, several smaller projects like “European Earthbuilder” and “Lehmbau Mobil” allowed to deepen the relations between the partners, to transfer the teaching materials into three more East European countries, and to exchange trainers and trainees. From 2007 to 2009 a follow up project “LearnWithClay” designed ECVET units for learning outcomes in the clay plaster sector. The outcomes of this project are european wide transparent and comparable certificats in earthbuilding, following the recommendations of the « European credit system for vocational education and training » (ECVET). The project designed six units : (1) Preparing clay plaster ; (2) Application of clay plaster ; (3) Surface treatments, maintenance and repair of clay plasters ; (4) Interior design with clay plaster ; (5) Decorative elements with clay plaster ; (6) The clay plaster market. Each unit can be assessed at different levels, according to the « European Qualification Framework » (EQF). Training centres across Europe are offering selected units on different levels. The six units of level 4 give you a certificate by a German crafts chamber. This qualification is accessible to experienced crafts people across Europe who can provide evidence of appropriate learning outcomes, skills and understanding.